4x+9+6x-3=180

Simple and best practice solution for 4x+9+6x-3=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+9+6x-3=180 equation:


Simplifying
4x + 9 + 6x + -3 = 180

Reorder the terms:
9 + -3 + 4x + 6x = 180

Combine like terms: 9 + -3 = 6
6 + 4x + 6x = 180

Combine like terms: 4x + 6x = 10x
6 + 10x = 180

Solving
6 + 10x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 10x = 180 + -6

Combine like terms: 6 + -6 = 0
0 + 10x = 180 + -6
10x = 180 + -6

Combine like terms: 180 + -6 = 174
10x = 174

Divide each side by '10'.
x = 17.4

Simplifying
x = 17.4

See similar equations:

| 2/3(z+1)+5/6(z-2)=8/9(z+3)+1 | | 8x-14y=-2 | | x+50=x+32 | | 145+3w=433 | | 6=-4x+5x+6 | | 5.73x-14.67x= | | 2x+2+4x=-57 | | -8d/2=-9d-20 | | 2(x+1)+1= | | x^2+7x^2-60x=0 | | 12+3b=30 | | 2+4x=3x-4 | | 0=16t*2+24t+3 | | 5x+1+3x-2=62 | | 12x+7y=9 | | h=16t*2+24t+3 | | 28=3a+7 | | 12b^3-15b^2= | | 49t^2+28t+4=0 | | p=b+41+3c | | 16=w^2+w | | -7-6z=8 | | 6f-5f=-28 | | 4+9= | | 2p+15-180=y | | 15=3-2X | | 32+2c=-1 | | 4*.75+7*n=13.25 | | 15y+4=34 | | M/4+8=17 | | .42=.048 | | -(3-6x/2)=4 |

Equations solver categories